Temperature-dependent bioaccumulation of polycyclic aromatic hydrocarbons. - Muijs, B.; Jonker, M.T.O. (American Chemical Society, 2009)
Bioaccumulation factors (BAFs) play a key role in risk assessment of chemicals in sediments and soils. For hydrophobic organic chemicals (HOCs), BAFs are, however, difficult to determine and values are mostly obtained by modeling. Apart from a lack of reliable data, the applicability of lab-derived values in the field situation is unknown, as exposure conditions (e.g., temperature, pH, salinity, test species, number of chemicals) are standardized in the lab, whereas they may vary in the field. In this study, the effect of temperature on the bioaccumulation of a series of moderate to very hydrophobic PAHs in aquatic worms was studied by using polydimethylsiloxane (PDMS)-coated solid phase microextraction (SPME) fibers. The results indicated that bioaccumulation of nonmetabolizable HOCs is an exothermic, enthalpy-driven process, thus decreasing with increasing temperature. As such, biotic concentrations may be several times higher in winter than in summertime, which could have ecotoxicological consequences. A two-parameter linear free energy relationship was derived with which PAH bioaccumulation can be predicted from temperature and the chemicals' hydrophobicities. Comparing the determined (thermodynamics of) PAH partitioning into organisms and PDMS indicated that the latter phase cannot be used as a surrogate phase for animal lipids. Still, SPME provides an appropriate analytical tool for the measurement of aqueous concentrations, from which bioaccumulation can subsequently be estimated by using BAFs.